Bacterial Profile of Middle Ear Fluid with Recurrent Acute Otitis Media Infection Using Culture Independent 16S rDNA Gene Sequencing - Nagaraj, Geetha; Girdhar, Anurag; Chinnappa, Jagdish; Ganaie, Feroze; Govindan, Vandana; Ravikumar, Kadahalli Lingegowda (Journal of Pediatric Infectious Diseases, 2019)
Background Recurrent otitis media is one of the common infections of childhood. The causative bacterial pathogen is one of the major risk factors of recurrent infection. With limited availability of Indian data, we performed this study to identify the bacterial pathogens.Materials and Methods Otitis media cases were diagnosed based on clinical criteria. Thirty-six middle ear fluid (MEF) samples were collected by tympanocentesis and cultured for pathogens. Seventy-eight per cent of the cases had three previous episodes of otitis media in the past 6 months; the remaining 22% had four episodes in the preceding 6 months. At the time of sample collection, all patients were on antibiotic coverage. Genomic DNA was extracted from MEF samples using Qiagen DNA mini Kit. The 16s rDNA polymerase chain reaction (PCR) and quantitative multiplex (qmPCR) for Streptococcus pneumoniae was performed on these samples. Streptococcus pneumoniae–positive samples were serotyped using PCRSeqTyping.Results None of the 36 samples showed growth by conventional culture. The 16s rDNA PCR identified bacterial pathogens in 33 samples. Four samples gave mixed reads. The organisms identified were Neisseria spp. other than Neisseriameningitidis (n = 7), N. meningitidis (n = 8), Lactococcus spp. (n = 5), S. pneumoniae (n = 2), Pseudomonas aeruginosa (n = 2), Haemophilus influenzae (n = 1), Salmonella infantis (n = 1), Staphylococcus epidermidis (n = 1), Staphylococcus auricularis (n = 1), and Streptococcus sp. (n = 1). The qmPCR detected the presence of S. pneumoniae in six samples. PCRSeqTyping was able to identify Serotype 19A in two samples positive for S. pneumoniae.Conclusion The study demonstrates the usefulness of 16s rDNA PCR protocol to identify the bacterial pathogens in MEF by a culture-independent method. Neisseria spp. were the predominant species identified followed by Lactococcus spp. and S. pneumoniae. Detection of pneumococci by 16s rDNA PCR correlated well with qmPCR-based detection and PCRSeqTyping.
Keywords: recurrent acute otitis media; bacterial etiology; 16s rDNA sequencing